2016
DOI: 10.1002/slct.201600228
|View full text |Cite
|
Sign up to set email alerts
|

Iodine(III)-Mediated Ring Contraction of 1,2-Dihydronaphthalenes: Mechanistic Insight by Computational Investigations

Abstract: The metal‐free synthesis of the trans‐1,3‐disubstituted indanes through the ring contraction of 1,2‐dihydronaphtalenes, promoted by PhI(OH)Ts (HTIB or Koser's reagent), was computationally studied using Density Functional Theory (DFT) methods. DFT calculations suggest that the stereoselectivity of these reactions arises through the torsional effects during the electrophilic addition of the hypervalent iodine to the double bond of the 1,2‐dihydronaphthalene. Furthermore, the fundamental role played by the solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In a previous computational study, we applied a continuum-microsolvation approach to describe the reaction mechanism involved in the ring contraction of 1,2-dihydronaphthalenes mediated by an iodine( iii ) compound. 74 Since then new theoretical studies have used the same approach exposing the relevance of solvent reactivity in hypervalent iodine-based reactions. 46,52,56,57…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous computational study, we applied a continuum-microsolvation approach to describe the reaction mechanism involved in the ring contraction of 1,2-dihydronaphthalenes mediated by an iodine( iii ) compound. 74 Since then new theoretical studies have used the same approach exposing the relevance of solvent reactivity in hypervalent iodine-based reactions. 46,52,56,57…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, in analogy to the methanol cluster previously reported, 74 we used continuum-microsolvation models composed by three molecules of water or methanol in order to evaluate the solvent effect in the nucleophilic addition of methanol to intermediate carbenium ion 14 , which has been previously suggested to be involved in the ring expansion reaction of methylene benzoannulenes (Scheme 3). 49…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RE and S N 2 pathways were also studied using microsolvation and cluster‐continuum solvation models where the solute–solvent interaction is better described compared to the PCM or the SMD solvent continuum models . The results showed that S N 2 mechanism is favored over RE route.…”
Section: Trifluoromethylationmentioning
confidence: 99%